The intercultural city : planning for diversity advantage - Wood, Phil, 1959- (Earthscan, 2008)
'This book reminds us - with both proof and passion - that there can be no truly creative or competitive cities without first having curiosity compassion conviviality and cooperation.' Richard Florida author of The Rise of the Creative Class 'A much-needed addition to the literature.' Kathy Pain director of Globalization and World Cities Spatial Planning Unit Loughborough University In a world of increasing mobility how people of different cultures live together is a key issue of our age especially for those responsible for planning and running cities. New thinking is needed on how diverse com.